A new species of Succinoraphidia Aspöck & Aspöck, 2004 (Raphidioptera: Raphidiidae) from the late Eocene Rovno amber, with venation characteristics of the genus - Perkovsky, Evgeny E.; Makarkin, Vladimir N. (Zootaxa, 2019)
Succinoraphidia radioni sp. nov. (Raphidiidae) is described from the late Eocene Rovno amber, Ukraine. The genus also includes two species from contemporaneous Baltic amber, i.e., S. exhibens Aspöck & Aspöck, 2004 and S. baltica (Carpenter, 1957), comb. nov. The venation of Succinoraphidia is analysed. It possesses several plesiomorphic character states at the family level, and the monotypic subfamily Succinoraphidinae represents a basal group within the family or possibly even a potential stem group of Raphidiidae. All diagnostic character states of Succinoraphidia (except the structure of the pterostigma) are found in a few Cretaceous species of the paraphyletic Mesoraphidiidae, but some of these are not found in the extant Raphidiidae.